Teacher’s Perception on the Implementation of Clustering Techniques Using Sticky Note Media in Teaching Writing Recount Text at the Tenth Grade of Senior High School - Ismil Mubarok; Rini Listyowati; Ina Daril Hanna (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study investigates the use of sticky note media and clustering approaches in the teaching of writing recount texts at SMAN 3 Pamekasan. When producing recount texts, many students struggle with concept organization and consistency. In order to overcome these obstacles, the instructor used sticky notes in conjunction with the clustering strategy to help the students write better. One English instructor at SMAN 3 Pamekasan was the subject of this qualitative case study, and information was gathered via documentation, semi-structured interviews, and observation. An interactive model that included data reduction, data display, and conclusion drawing was used to examine the data. According to the results, students’ creativity and organizational skills were greatly enhanced by the clustering technique using sticky notes. Sticky notes' adaptability and visual format made it easier for pupils to organize and link their ideas. The teachers thought well of the approach, observing a rise in student engagement and motivation. Modeling and guided practice helped to overcome the initial bewilderment of the students and the restricted availability of materials. The study comes to the conclusion that this method supports critical thinking and active involvement in addition to improving students' writing skills, which is in line with curriculum objectives.